Generic Path Planning Algorithm for Mobile Robots Based on Bézier Curves - Costanzi, Riccardo; Fanelli, Francesco; Meli, Enrico; Ridolfi, Alessandro; Allotta, Benedetto (IFAC-PapersOnLine, 2016)
The availability of an efficient and reliable path planning strategy is a great benefit to mobile robots. Being able to intelligently connect a series of waypoints is a crucial requirement for the execution of autonomous navigation tasks. Several performance indices can be used to evaluate the goodness of a path, including its length and smoothness. In this paper, the authors focus on planar path planning for mobile robots; Bézier curves are employed, optimizing the computed path with respect to length and curvature, the latter used as a measure of smoothness. Due to the complexity of the objective function, optimization is performed by means of a direct search method. The proposed approach aims at generating paths offering advantages to mobile robots navigation in terms of controllability and reducing the related power consumption. The performed tests show that the presented method allows to achieve interesting results, suggesting its viability as a suitable path planning strategy for different kinds of mobile robots.